How to Alleviate MICE Students’ Foreign Language Speaking Anxiety for Internship and Job Interview in English? - Yayan Fitriansyah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
In the increasingly globalized tourism and hospitality industry, English proficiency has become a critical skill, particularly for students pursuing careers in Meetings, Incentives, Conventions, and Exhibitions (MICE). However, many students at Palembang Polytechnic of Tourism continue to experience Foreign Language Speaking Anxiety (FLSA), which hinders their performance during internships and job interviews. This study aims to explore the underlying factors contributing to FLSA and to identify effective strategies to alleviate it, especially in the context of English for professional purposes A qualitative secondary research method was employed through a Systematic Literature Review (SLR), analyzing 21 peer-reviewed articles published between 2015 and 2024. Articles were selected based on their relevance to English language learning, anxiety in speaking, and vocational education, particularly in tourism and hospitality. Thematic analysis was applied to identify recurring causes, pedagogical interventions, and best practices. The findings revealed that FLSA is primarily caused by low language proficiency, lack of self-confidence, insufficient real-life communication practice, and fear of negative evaluation (Sartika, S., & Arniati, 2023; Shirvan & Talebzadeh, 2017). However, the implementation of learner-centered strategies such as cooperative learning, role-playing, technology-enhanced instruction (MALL and CALL), and authentic speaking simulations showed significant potential in alleviating anxiety. Moreover, aligning English teaching content with real MICE communication tasks—such as presentations, complaint handling, and formal interviews—was found to enhance both language fluency and student confidence. Alleviating FLSA requires not only linguistic instruction but also emotional support and context-based language training. This study recommends that English lecturers and curriculum designers adopt holistic approaches that address both communicative competence and affective readiness to better prepare MICE students for global professional environments.